Update on mammalian sperm capacitation: how much does the horse differ from other species?. Issue 5 (May 2019) - Leemans, Bart; Stout, Tom A E; De Schauwer, Catharina; Heras, Sonia; Nelis, Hilde; Hoogewijs, Maarten; Van Soom, Ann; Gadella, Bart M
Abstract : In contrast to various other mammalian species, conventional in vitro fertilization (IVF) with horse gametes is not reliably successful. In particular, stallion spermatozoa fails to penetrate the zona pellucida, most likely due to incomplete activation of stallion spermatozoa (capacitation) under in vitro conditions. In other mammalian species, specific capacitation triggers have been described; unfortunately, none of these is able to induce full capacitation in stallion spermatozoa. Nevertheless, knowledge of capacitation pathways and their molecular triggers might improve our understanding of capacitation-related events observed in stallion sperm. When sperm cells are exposed to appropriate capacitation triggers, several molecular and biochemical changes should be induced in the sperm plasma membrane and cytoplasm. At the level of the sperm plasma membrane, (1) an increase in membrane fluidity, (2) cholesterol depletion and (3) lipid raft aggregation should occur consecutively; the cytoplasmic changes consist of protein tyrosine phosphorylation and elevated pH, cAMP and Ca 2+ concentrations. These capacitation-related events enable the switch from progressive to hyperactivated motility of the sperm cells, and the induction of the acrosome reaction. These final capacitation triggers are indispensable for sperm cells to migrate through the viscous oviductal environment, penetrate the cumulus cells and zona pellucida and, finally, fuse with the oolemma. This review will focus on molecular aspects of sperm capacitation and known triggers in various mammalian species. Similarities and differences with the horse will be highlighted to improve our understanding of equine sperm capacitation/fertilizing events.